2011
DOI: 10.1167/11.14.14
|View full text |Cite
|
Sign up to set email alerts
|

Contrast integration over area is extensive: A three-stage model of spatial summation

Abstract: Classical studies of area summation measure contrast detection thresholds as a function of grating diameter. Unfortunately, (i) this approach is compromised by retinal inhomogeneity and (ii) it potentially confounds summation of signal with summation of internal noise. The Swiss cheese stimulus of T. S. Meese and R. J. Summers (2007) and the closely related Battenberg stimulus of T. S. Meese (2010) were designed to avoid these problems by keeping target diameter constant and modulating interdigitated checks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…Nonetheless, we envisage extended integration where appropriate, and we have presented evidence for this elsewhere (e.g. Baker & Meese, 2011). However, from one point of view, the generic model that we propose might appear puzzling: what is the point of integrating signal over a stimulus dimension if it is then to be suppressed by a similar integration over the same dimension?…”
Section: Discussionmentioning
confidence: 88%
“…Nonetheless, we envisage extended integration where appropriate, and we have presented evidence for this elsewhere (e.g. Baker & Meese, 2011). However, from one point of view, the generic model that we propose might appear puzzling: what is the point of integrating signal over a stimulus dimension if it is then to be suppressed by a similar integration over the same dimension?…”
Section: Discussionmentioning
confidence: 88%
“…In light of current results, motion biases may be a product of motion detector recruitment, which is aborted when a motion detector chain is interrupted. In addition, it has been suggested that the summation of detector information in motion recruitment is linear [8], [29]. The centripetal bias during motion with spatial decorrelations can be the result of a linear spatial integration, given an ineffective disruption of the motion detector chain in the periphery of the stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Such an arrangement predicts a triplet of pedestal masking functions, similar to those found here (see Figure A1d in Appendix A). However, there is little or no evidence for such broad tuning at this low level in the hierarchy in the spatial domain (Baker & Meese, 2011a) or in the orientation domain (see Meese & Baker, 2011b, for a review), where receptive fields in the primary visual cortex (filter elements) have a small number of lobes (i.e. are selective to very few stimulus cycles) and are orientation tuned (DeValois & DeValois, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this approach was to clamp the level of internal noise so as to achieve a clean measure of the integration process. In conjunction with extensive modelling, these experiments provided good evidence for narrowband spatial filtering (Meese, 2010), followed by a square-law contrast transducer (Meese, 2010; Meese & Summers, 2009), additive noise and linear summation (integration) of image contrast (Meese, 2010; Meese & Baker, 2011a) that extended over nine or more stimulus cycles (Baker & Meese, 2011). Various models of spatial probability summation (i.e.…”
Section: Introductionmentioning
confidence: 89%